PhonoMetric: a dual-metric engine for real-time English language accent evaluation and personalized speech training for Indian learners - Soundarraj, Rajkumaran; Anantharajan, Shenbagarajan; Loganathan, Saranraj (Frontiers in Communication, 2026)
The core objective of this study is to develop a novel method to measure and improve standard spoken English pronunciation accuracy in relation to a desired accent style using current speech processing and information retrieval methods. The system employs the ECAPA-TDNN model, which has been fine-tuned with American-accented speech to create speaker embeddings from the user’s audio. Accent embeddings from reference accent speech samples are subsequently compared using cosine similarity to arrive at an Accent Similarity Score (ASS). At the same time, the user speech is transcribed using the Whisper ASR model (open-source software), then aligned using a forced alignment tool with a reference sentence at the phoneme level. In automatic classification, the level of proficiency (Beginner, Intermediate, Advanced) is attributed to the users on the basis of semantic and phonetic closeness and measures of comprehensible mistakes. For training, the system utilizes the user’s fluency profile to create a particular YouTube query through SerpAPI, providing related and quality resources for pronunciation, their native and accent gaps being considered. An experimental study was conducted among 30 undergraduate students. Experimental evaluations have shown that our two-metric engine provides a scalable and adaptable solution to real-time accent evaluation with classification accuracy of 91.3, 88.6, and 93.1% across beginner, intermediate, and advanced users, respectively. The system provided a strong negative correlation (r = −0.82) between PER and ASS, while indicating that users received a score of 4.6/5 on satisfaction in initial usability studies.